Push-Pull Factors of Migration amidst Domestic Resistance of the Visegrad Group Countries - Cahya Puja Ayu Shintawati; Yoga Suharman (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
This research presents the push-pull factors of refugees and asylum seekers towards Europeancountries during strong domestic resistance by The Visegrad Group, consisting of Hungary, Poland,Slovakia, and the Czech Republic. These factors were examined using the push-pull migration theory,and the results are presented qualitatively. The data and information presented in this paper came fromsecondary sources. The findings revealed two significant facts. Firstly, the negative conditions in thehome countries of refugees and asylum seekers act as migration drivers, including prolonged conflicts,economic crises, and limited job opportunities; secondly, the attractiveness of Europe as a regioncharacterized by safety, a stable economy, availability of resources, and sufficient job opportunities.